The Effect Of Vulva Hygiene Monopoly Simulation Game On Vulva Hygiene Behavior In Teenagers At The Dormitory Of MAN 2 Yogyakarta - PERTIWI HIDAYATI, AYU PUTRI (Infomasi dan Promosi Kesehatan, 2024)
Advanced adolescents are in the age range of 17-21 years when physical changes occur, one of which is the reproduction ability. Efforts that can be made are to carry out proper vulva hygiene. In Indonesia, 43.3 million female adolescents have very poor vulva hygiene. One of the impacts of improper vulva hygiene is vaginal discharge. In 2013, 75% of 237,641,326 women experienced vaginal discharge. In 2008, out of 43.3 million teenagers aged 15-24 years had unhealthy behavior, resulting in vaginal discharge. According to static data in DIY in 2009, 68% of 2.9 million teenagers aged 15-24 years experienced vaginal discharge. Behavior can be changed with new habits and additional insight. Games can be a learning medium, one of which is monopoly. The study aimed to determine the effect of the vulva hygiene monopoly simulation game on vulva hygiene behavior in adolescents in the MAN (State Islamic High School) 2 Yogyakarta dormitory. The research employed quantitative research using an experimental research design, namely pre-experimental design with pre test-post test design. This study used a quantitative approach with a total of 39 respondents. The Wilcoxon test shows that there is an influence of the monopoly vulva hygiene simulation game on vulva hygiene behavior with a p value of 0.00 so that there is an influence of the monopoly vulva hygiene simulation game on vulva hygiene behavior, with good behavior of 46.2% and fair behavior of 53. .8%, while behavior after good was 100%. The results of this research show that there is an influence of the monopoly vulva hygiene simulation game on vulva hygiene behavior in teenagers in MAN 2 Yogyakarta dormitory.